Exploring the connection between adolescent identity and well-being in vocational scope - Nisa, Khoirun (INVOTEC, 2023)
Adolescence is a significant period starting with mental, emotional development and physical development; adolescents experience many problems due to unfulfilled levels of welfare subject. Because the level of youth welfare also measures the progress of a country, a country also has a responsibility to improve the welfare of its youth. For this reason, this study aims to find which adolescent welfare domain subjects need more attention. Research on youth welfare uses the bibliometric analysis method with the help of the VOS Viewer application system using the keyword "Wellbeing for youth" using the limitations of the type of journal articles in English that have been published in the last five years and obtained as many as 840 data with 114 keyword verifications. Used to visualize bibliometric maps. The results of research that has been conducted from 114 keywords, mental health, which is one of the subject domains of welfare, is a keyword that is often researched in the last five years, and the country with the highest level of research on adolescent interest is the United States and in followed by the United Kingdom and followed by several other developed countries.